Representações gráficas procedimentais: elementos e relações - Mazur Damacena, Diovana; Cristine Assis da Silva Smythe, Kelli (InfoDesign, 2021)
This paper presents an analysis of graphic representations aimed to understand the form of structuring and relationship used in the compositions. For this end, from a literature review, a graphic analysis of ten procedure representations was performed. The analysis was based on syntactic and semantic variables from Engelhardt’s (2002) theory of graphic syntax, contemplating representations of different levels of complexity. The data was analyzed quantitatively, identifying elements and relationships used in this type of representation. The results contributed to identification of useful requirements for the development of procedural representations.